Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð½Ð° ÑÐ¾Ñ…Ñ€Ð°Ð½Ð½Ð¾ÑÑ‚ÑŒ ÑƒÐ»ÑŒÑ‚Ñ€Ð°ÑÑ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ñ‹ Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ - Repin, N. V.; Govorukha, T. P.; Strona, V. I.; Yurchenko, T. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
Placental ultrastructure was studied after cryopreservation. It has been shown that low temperature preservation with DMSO as cryoprotectant provides better integrity of placenta cells’ ultrastructure.